Magnetic and electromagnetic absorption properties of FeNi alloy nanoparticles supported by reduced graphene oxide. Issue 2 (29th November 2013) - Sun, Chen; Jiang, Wei; Wang, Yujiao; Sun, Danping; Liu, Jie; Li, Pingyun; Li, Fengsheng
Abstract FeNi alloy nanoparticles (NPs) supported by reduced graphene oxide (RGO) (FeNi/RGO nanocomposites) were successfully synthesized through in‐situ reduction. Large amounts of sphere‐like FeNi NPs are uniformly deposited on the RGO nanosheets. The magnetic hysteresis measurement reveals the ferromagnetic behavior of the nanocomposites at room temperature. According to the electromagnetic (EM) characteristics, the FeNi/RGO nanocomposites show outstanding EM absorption properties in the 2–18 GHz range, as evidenced by the wide effective absorption bandwidth (up to 3.3 GHz, with reflection loss RL < –10 dB) and a minimal RL (–32 dB) at 12.4 GHz with a thickness of 1.5 mm. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)